(untitled) (International Journal of Engineering and Computer Science, 2018)
MANET is a infrastructure less communication network system. Power saving is the greater issue in Mobile Ad-hoc Networks because nodes are power constrained due to limited battery power supply. Pointing at energy constrained of Mobile Ad-Hoc Networks, this paper proposes an Energy Saving Multipath AODV routing protocol, which based on node residual energy and Threshold value based scheme for selecting only two paths that have maximum energy value . Choose one path from two of them that have maximum energy for communication and second path is reserve for future use as alternate route. So, when main route is no longer in use due to link failure, energy exhaustion second route is used for data transmission which conserve energy consumed in reroute initiation process. Simulation results shows that it shows better performance in terms of Packet Delivery Ratio and End-to-End delay in comparison to AODV routing protocol. The proposed work is verified using MATLAB simulator.